The aquatic hazard of hydrocarbon liquids and gases and the modulating role of pressure on dissolved gas and oil toxicity. (August 2018) - Paquin, Paul R.; McGrath, Joy; Fanelli, Christopher J.; Di Toro, Dominic M.
Abstract: Hydrostatic pressure enhances gas solubility and potentially alters toxicity and risks of oil and gas releases to deep-sea organisms. This study has two primary objectives. First, the aquatic hazard of dissolved hydrocarbon gases is characterized using results of previously published laboratory and field studies and modeling. The target lipid model (TLM) is used to predict effects at ambient pressure, and results are compared to effect concentrations derived from extrapolation of liquid alkane hazard data. Second, existing literature data are used to quantify and predict pressure effects on toxicity using an extension of the TLM framework. Results indicate elevated pressure mitigates narcosis, particularly for sensitive species. A simple adjustment is proposed to allow TLM-based estimates of acute effect and TLM-derived HC5 values (concentrations intended to provide 95% species protection) for oil or gas constituents to be calculated at depth. Future applications, and opportunities and challenges for providing validation, are discussed. Highlights: Hydrostatic pressure may alter risks of oil and gas releases to deep-sea organisms. Elevated pressure has been shown to mitigate narcotic effects on tadpoles. This influence may be represented in the target lipid model, to predict effects. The predicted pressure dependency is more significant for sensitive species. Testing and validation of these results with deep-sea biota will be challenging.